Association Mapping of Salinity Tolerance in Rice Using Molecular Markers - Pushparajan, N.; Krishnasamy, V.; Babu, R. Chandra; Kannanbabu, J. R. (International Journal of Bio-resource and Stress Management, 2011)
A study was conducted to determine the association between simple sequence repeat (SSR) markers and salt tolerance QTLs qSKC-1 and qSNC-7 in rice. Genetic variability for salt tolerance among 172 rice accessions was assessed using two physiological indices viz., shoot potassium concentration (SKC) and shoot sodium concentration (SNC). A wide range of variance for the two indices indicated the existence of substantial genetic diversity for salt tolerance among the germplasm studied. Eight SSR markers near SKC QTL (qSKC-1) locus on chromosome 1 and six SSR markers near SNC QTL (qSNC-7) locus on chromosome 7 were selected. Dendrogram constructed based on physiological traits and SSR marker data grouped the rice accessions into salt tolerant, moderately tolerant and susceptible lines. Marker-trait associations were studied for the two physiological traits using a set of 40 polymorphic SSR loci, 26 polymorphic loci for SKC QTL and 14 polymorphic loci for SNC QTL. Association mapping strategy identified four loci significantly associated with qSKC-1 QTL and two loci associated with qSNC-7 QTL by simple linear as well as multiple regression analyses. Marker loci identified in the present study may be useful for MAS, map based cloning of salt tolerance genes and functional genomics studies.